Analisis Perancangan Penstock PLTMH di Eremerasa Kabupaten Bantaeng Dengan Menggunakan ANSYS - Suryanto Suryanto; Apollo Apollo; Muhammad Julham Hamzah; Titiek Israwati (Politeknik Negeri Ujung Pandang, 2019)
Penstock acts as a distributor of fluid flow between the tank and the turbine. The aims of this study are to determine the characteristics of the pressure and the water velocity and flow pattern that occurs in the penstock and to determine the efficiency of hydraulic optimum turbine with design power 40 kW. Characteristics are analyzed by simulation using Ansys fluent software. The simulation results assist in the design process and design of water turbines penstock accurately and shorten the time. Based on the simulation results in the penstock, the pressure varies on along the penstock and maximum occur on the inlet side (33652 Pa) and then gradually drops along the pipeline and reach the minimum conditions on the outlet side (2651 Pa). Characteristics of the fluid velocity tends to be constant from the inlet side to the outlet side (2,46 m/s), but there are fluctuations in flow velocity in the bend of 10° and 45°. The pattern of the flow of water along the penstock pipe turbulent, especially in connection with angle bends 45° and 10°. Angle turn follow the existing topography. Additionally, it obtained maximum turbine power of 50,617 kW with hydraulic efficiency of 68.93% and the effective height of the turbine is equal to 17,234 m and a discharge of 0,3 m3/s.